Brazil, 40 Years of Struggles Over Political Legitimacy Through the Lenses of Representation. Issue 3 (3rd July 2019) - Mendonça, Ricardo Fabrino; Gurza Lavalle, Adrian
ABSTRACT: This editorial introduction aims to show the dialogue between the literature on representation and the research that has been conducted in Brazil, paying special attention to how these theoretical debates have displaced key understandings on the study of political phenomena in Brazil. These very same phenomena have served, however, as points of friction for existing international debates as well. The text starts with a brief introduction to the concept of political representation and the contemporary agendas that were fuelled by the scholarship seeking to pluralise it. It, then, discusses debates about representation in Brazil, focusing on key agendas in which Brazilian scholars have offered contributions to the international literature. Lastly, it provides an overview of the articles making up this special issue, outlining their main arguments and contributions.